Inovasi Kurikulum Integratif Pesantren sebagai Respons terhadap Tantangan Globalisasi: Studi di Pondok Pesantren Darul Amanah Bedono Kabupaten Semarang - Ahmad Mustafidin; Aliwan; Moh Fahsin; Abdul Hakim; M. Arief Hidayatullah (At Turots: Jurnal Pendidikan Islam, 2025)
Globalization presents new and complex challenges for the educational sector, particularly for traditional institutions such as Islamic boarding schools (pesantren). This study critically examines the concept, structure, and implementation strategies of an integrative curriculum innovation developed at Pondok Pesantren Darul Amanah Bedono, located in Semarang Regency, as a strategic response to these challenges. Employing a descriptive qualitative methodology, data were collected through field observations, in-depth interviews with school leaders, teachers, and students, as well as analysis of curriculum documents and learning activities. The findings reveal that the pesantren has successfully designed and implemented an integrative curriculum model that combines the traditional diniyah curriculum—rooted in classical Islamic texts (kitab kuning)—with a national-standard general education curriculum. This integration is manifested not only in the content of instruction but also in management systems, pedagogical methods, and character education. By integrating spiritual, academic, and life skill dimensions, the curriculum innovation effectively addresses both the local needs of the pesantren and the global demands of contemporary education. Key strategies include balanced learning schedules, teacher professional development in integrative pedagogy, and the use of information technology to enhance the learning process. Moreover, the implementation of contextual and project-based learning approaches fosters the development of independent, critical, and collaborative learners. External collaborations with educational institutions and active alumni engagement further support the success of this initiative. Substantively, the integrative curriculum contributes to the production of pesantren graduates who excel in religious knowledge while also possessing essential 21st-century competencies such as digital literacy, intercultural communication, and critical thinking. Foundational pesantren values—such as tawadhu’ (humility), discipline, and sincerity—remain deeply embedded within this progressive transformation. This study suggests that the integrative curriculum model should be continuously refined and adapted in accordance with evolving socio-educational contexts through internal policy innovation, governmental support, and strengthened inter-pesantren networks. Such efforts are vital to ensuring the strategic role of pesantren in cultivating religious, adaptive, and globally competitive future generations.